Modeling and analysis of dynamic systems - Esfandiari, Ramin S.; Lu, Bei (CRC Press / Taylor & Francis Group, 2014)
Modeling and Analysis of Dynamic Systems, Second Edition introduces MATLAB®, Simulink®, and Simscape™ and then uses them throughout the text to perform symbolic, graphical, numerical, and simulation tasks. Written for junior or senior level courses, the textbook meticulously covers techniques for modeling dynamic systems, methods of response analysis, and provides an introduction to vibration and control systems. These features combine to provide students with a thorough knowledge of the mathematical modeling and analysis of dynamic systems.See What’s New in the Second Edition:Coverage of modeling and analysis of dynamic systems ranging from mechanical to thermal using SimscapeUtilization of Simulink for linearization as well as simulation of nonlinear dynamic systemsIntegration of Simscape into Simulink for control system analysis and designEach topic covered includes at least one example, giving students better comprehension of the subject matter. More complex topics are accompanied by multiple, painstakingly worked-out examples. Each section of each chapter is followed by several exercises so that students can immediately apply the ideas just learned. End-of-chapter review exercises help in learning how a combination of different ideas can be used to analyze a problem.This second edition of a bestselling textbook fully integrates the MATLAB Simscape Toolbox and covers the usage of Simulink for new purposes. It gives students better insight into the involvement of actual physical components rather than their mathematical representations